Firmness of multifractal spectra of relative change of brightness, turn and image scale - Лотиш, Володимир В’ячеславович; Разкевич, Петро Васильович (Eastern-European Journal of Enterprise Technologies, 2010)
Verification of multifractal spectra descriptions is conducted in relation to transformation of image: change a brightness, turn in relation to a center and down-scaling. The graphs of firmness are rotined in relation to each of transformations.